Efficacy of targeted treatment beyond third-line therapy in metastatic kidney cancer: retrospective analysis from a large-volume cancer center - Vallet, Sonia; Pahernik, Sascha; Tosev, Georgi; Hadaschik, Boris; Duensing, Stefan; Sedlaczek, Oliver; Hohenfellner, Markus; Jäger, Dirk; Grüllich, Carsten (Clinical genitourinary cancer, 2015)
Introduction/background, currently, 7 agents are approved for the first- and second-line therapy for metastatic renal cell carcinoma. In contrast, data supporting their use beyond second line are limited. Here we summarize our experience in patients treated with more than 4 lines of therapy. Methods: we retrospectively assessed the outcome of 24 patients treated at our institution with at least 4 lines of therapy. Progression-free survival (PFS) and overall survival (OS) were calculated using Kaplan-Meier estimates.Results: Median OS from the initiation of first-line therapy for the whole cohort is 64.7 months. Up to 96% of the patients received a tyrosine kinase inhibitor (TKI) and mammalian target of rapamycin (mTOR) inhibitor (mTOR-I) within the first 3 lines of treatment. In the fourth or following lines, patients were treated with TKI, mTOR-I, bevacizumab/interferon, or experimental drugs. Seven patients continued treatment with a sixth-line agent; one has been treated up to the ninth line. Sixteen percent of the patients receiving fourth-line therapy and 13% receiving fifth-line therapy experienced a partial remission, which was independent from response to previous therapies. Median OS from fourth and fifth line was 30.8 and 26.2 months, respectively. Median PFS for fourth-line therapy was 5.8 months. No significant difference in PFS was observed for patients with disease that responded or did not respond to first-line therapy. Conclusion: Despite the limitations of a retrospective analysis, our study suggests that selected patients benefit from multiple lines of treatment, independent of response to first-line therapy. However, the optimal sequence of treatment with regard to later lines remains to be determined.